The Role of Prophet Muhammad on Women Emancipation in Mecca Period - Shidqy Munjin; Ihsan Kamaludin (Islam Realitas: Journal of Islamic and Social Studies, 2019)
Islam as one of the religions in the world has several types of social interaction. The way of interaction is called silaturahmi, one of the most pivotal topics in it is communication among Moslem start from Prophet Muhammad spread the Islamic values including in terms of social treatment to others. This article focuses on Prophet Muhammad endeavor for women’s emancipation, the struggle begins with the Mecca period until he died. The studying aim is to find out in-depth the prophet Muhammad method and the impact of a social system in there. The method used in this study is descriptive qualitative research expected to be able to reveal qualitative information with description-analysis using the strategy used in this research is a case study. The result indicates the guidance and awareness of women emancipation through the prophet Muhammad strategies pose a huge impact on belief in improving women position in society using the thoughts of feelings and actions in accordance with the teachings of religion in the context of Islam the teachings of revealed Book “ the Quran and the Sunnah”.Islam sebagai salah satu agama yang memiliki beberapa tipe interaksi sosial. Cara interaksi tersebut dikenal dengan istilah silaturahmi, salah satu topik paling utama di dalam komunikasi antara muslim dimulai semenjak Nabi Muhammad menyebarkan nilai keislaman termasuk dalam hal perlakuan sosial kepada orang lain. Artikel ini fokus kepada upaya Nabi Muhammad dalam emansipasi perempuan, usaha tersebut dimulai pada periode Mekah hingga ia meninggal. Penelitian ini bertujuan untuk memahami metode Nabi Muhammad dan dampaknya terhadap sistem sosial pada masa tersebut. Metode yang digunakan adalah penelitian kualitatif yang diharapkan mampu untuk mengungkap informasi kualitatif dengan analisa deskriptif menggunakan cara studi kasus. Hasil penelitian ini menunjukan bahwa bimbingan dan kepedulian terhadap emansipasi perempuan melalui strategi Nabi Muhammad memberikan dampak yang signifikan dalam peningkatan posisi perempuan di dalam masyarakat menggunakan pemikiran dan tindakan yang sesuai dengan ajaran agama Islam yaitu “Al-Quran dan Sunnah”.